A Gamified Social Media–Based Head and Neck Radiology Education Initiative of the American Society of Head and Neck Radiology: Viewership and Engagement Trends at 3 Years - Koontz, N.A.; Tomblinson, C.M.; Shatzkes, D.R.; Glastonbury, C.M.; Phillips, C.D.; Dean, K.; Strauss, S.; Agarwal, M.; Robson, C.D.; Wiggins, R.H. (American Journal of Neuroradiology, 2022)
BACKGROUND AND PURPOSE: Social media has made inroads in medical education. We report the creation and 3-year (2018–2021) longitudinal assessment of the American Society of Head and Neck Radiology Case of the Week (#ASHNRCOTW), assessing viewership, engagement, and impact of the coronavirus disease 2019 (COVID-19) pandemic on this Twitter-based education initiative.MATERIALS AND METHODS: Unknown cases were tweeted from the American Society of Head and Neck Radiology account weekly. Tweet impressions (number of times seen), engagements (number of interactions), and new followers were tabulated. A social media marketing platform identified worldwide distribution of Twitter followers. Summary and t test statistics were performed.RESULTS: #ASHNRCOTW was highly visible with 2,082,280 impressions and 203,137 engagements. There were significantly greater mean case impressions (9917 versus 6346), mean case engagements (1305 versus 474), case engagement rates (13.06% versus 7.76%), mean answer impressions (8760 versus 5556), mean answer engagements (908 versus 436), answer engagement rates (10.38% versus 7.87%), mean total (case + answer) impressions (18,677 versus 11,912), mean total engagements (2214 versus 910), and total engagement rates (11.79% versus 7.69%) for cases published after the pandemic started (all P values < .001). There was a significant increase in monthly new followers after starting #ASHNRCOTW (mean, 134 versus 6; P < .001) and significantly increased monthly new followers after the pandemic started compared with prepandemic (mean, 178 versus 101; P = .003). The American Society of Head and Neck Radiology has 7564 Twitter followers throughout 130 countries (66% outside the United States).CONCLUSIONS: Social media affords substantial visibility, engagement, and global outreach for radiology education. #ASHNRCOTW viewership and engagement increased significantly during the COVID-19 pandemic.ASHNRAmerican Society of Head and Neck Radiology#ASHNRCOTWASHNR Case of the Week hashtag@ASHNRSocietyASHNR Twitter account handleERengagement rateGIFGraphics Interchange FormatCOVID-19coronavirus disease 2019